A review: evolution of big data in developing country - Prasetyo, Bayu; Aziz, Faiz Syaikhoni; Faqih, Kamil; Primadi, Wahyu; Herdianto, Roni; Febriantoro, Wicaksono (Association for Scientific Computing Electrical and Engineering, 2019)
The development of technology from year to year is increasingly rapid and diverse. All systems that exist in human life began to be designed with technology that requires large data storage. Big Data technology began to be developed to accommodate very large data volumes, rapid data changes, and very varied. Developing countries are starting to use Big Data a lot in developing their systems, such as healthcare, agriculture, building, transportation, and various other fields. In this paper, it explains the development of Big Data applied to the sectors previously mentioned in developing countries and also the challenges faced by developing countries in the process of developing their systems.